Clinical labeling and imaging of transplanted CD133+ /CD34+ stem cells in patients with ischemic heart disease - Ghodsizad, Ali; Ruhparwar, Arjang; Karck, Matthias (The heart surgery forum, 2012)
The application of somatic stem cells has been shown to support the recovery of the myocardium in end-stage heart failure. A novel method for the intraoperative isolation and labeling of bone marrow-derived stem cells was established. After induction of general anesthesia, up to 400 mL of bone marrow were harvested from the posterior iliac crest and processed in the operating room under good manufacturing practice conditions by means of the automated cell-selection device Clini-MACS (Miltenyi Biotec). We subsequently injected autologous CD133+ and CD34+ stem cells in a predefined pattern around the laser channels in patients undergoing coronary artery bypass surgery and transmyocardial laser procedures. Intraoperative isolation and labeling is an effective cell-separation tool for the future, considering that novel cell markers can be promising new candidates for cell therapy.